2016
DOI: 10.7863/ultra.16.01074
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Assessment of Examiner Experience and the Accuracy of Sonographic Fetal Weight Estimation at Term

Abstract: These findings indicate the great importance of continuous quality control systems in sonographic weight estimation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
0
8
0
1
Order By: Relevance
“…study demonstrated a similar effect of experience on the accuracy of sonographic weight estimation, with a decrease in diagnostic performance in terms of a clear tendency toward underestimation after approximately 200 scans until the end of the study period. 17 A possible explanation for this unexpected result may be found in the fact that fetal biometry is considered by many as a basic diagnostic procedure, for which once a certain degree of experience has been gained, attention to detail may be lost, resulting in reduced accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…study demonstrated a similar effect of experience on the accuracy of sonographic weight estimation, with a decrease in diagnostic performance in terms of a clear tendency toward underestimation after approximately 200 scans until the end of the study period. 17 A possible explanation for this unexpected result may be found in the fact that fetal biometry is considered by many as a basic diagnostic procedure, for which once a certain degree of experience has been gained, attention to detail may be lost, resulting in reduced accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…In a former study, we could already demonstrate a nonlinear effect of experience on the accuracy of sonographic weight estimation, with a decrease in diagnostic performance after approximately 200 scans . However, in that study, measurements of the different biometric parameters were not evaluated separately.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…SDP sein. Auch für den Einfluss der Qualifikation des Arztes konnten wir keine Signifikanz nachweisen, obwohl in der Literatur oftmals ein klarer Zusammenhang zwischen dem Erfahrungsgrad des Untersuchers und dem Schätzfehler, zu Gunsten eines höheren Ausbildungsstandes, genannt wird [36]. Für den maternalen BMI, als mögliche Einflussgröße auf die Schätzgenauigkeit, konnte eine sichere Verschlechterung der sonographischen Schätzung ab einem Wert ≥ 25 kg/m² gezeigt werden [37].…”
Section: Diskussionunclassified
“…However, prior to a methodology's becoming common practice, there is often a so-called learning curve, or a period of time during which experience is gathered and proficiency is attained. [49][50][51] Because the identification of clinically significant STevents requires knowledge and repeated training, we believe that a learning curve exists in the incorporation of the method into routine clinical practice.…”
Section: Introductionmentioning
confidence: 99%